Analisis Kualitas Udara Karbon Monoksida Akibat Tingkat Kepadatan Kendaraan Lalu Lintas: (Studi Kasus: Jalan Sao Sao Kota Kendari) - Murdi, Murdi; Rosdiana, Rosdiana; Assiddieq, Moch. (Universitas Muhammadiyah Kendari, 2024)
Motorized vehicles are the main source of exhaust emissions which cause air pollution and reduce air quality due to several factors such as vehicle type, vehicle age, temperature threshold and altitude. Sao Sao Road has a single lane road, so the level of traffic density produces quite high exhaust gas emissions due to several factors such as the presence of shopping centers, educational institutions, tourist attractions and government. CO concentration measurements were carried out using a measurement procedure method that refers to SNI 19-7117.10-2005, using Impinger. In the measurements in the morning, afternoon and evening, the CO gas concentration reached 3000 µg/m³, 9435 µg/m³, and in the afternoon 7000 µg/m³, the CO concentration was still safe for life and the environment because it had not exceeded the quality standard, namely 10,000 µg/m³.